1979
DOI: 10.1007/bf01434628
|View full text |Cite
|
Sign up to set email alerts
|

Results of the searches for superheavy nuclei in the Cheleken Penninsula geothermal waters

Abstract: The water rich in heavy volatile metals form the Cheleken Penninsula hot springs was passed through a column containing 850kg of anion exchange resin. The spontaneous fission activity (SF) of the samples was measured by neutron multiplicity detectors. The counting rate of spontaneous fission events was 0.5 per day for 9 kg of saturated resin. After 170kg of the resin had been treated with acid solutions and hydroxides had been precipitated from the eluate with alkali, the counting rate for the precipitate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 4 publications
1
17
2
Order By: Relevance
“…For an assumed value of ~=8, the The results reported by Flerov et al [1] and our results reported here do not readily lend themselves to a direct comparison. Whereas we examined the predominantly sulfide precipitate collected at the Atlantis-II site, they investigated the waters from the Cheleken hot springs by first passing that concentrated salt solution through an ion exchanger followed by an elution procedure designed to collect the largest part of the heavier elements in the brine.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…For an assumed value of ~=8, the The results reported by Flerov et al [1] and our results reported here do not readily lend themselves to a direct comparison. Whereas we examined the predominantly sulfide precipitate collected at the Atlantis-II site, they investigated the waters from the Cheleken hot springs by first passing that concentrated salt solution through an ion exchanger followed by an elution procedure designed to collect the largest part of the heavier elements in the brine.…”
contrasting
confidence: 58%
“…In a recent study of hot brines from the Cheleken Penninsula, Flerov and co-workers [1,2] report observations of spontaneous fission activities. These results have led them to conclude that the most likely interpretation of their observation is the existence of a new naturally occurring isotope of a superheavy element.…”
mentioning
confidence: 96%
“…In the experiment described here we have not succeeded in reaching a sensitivity comparable to that of previous measurements with other thermal waters [1]. This fact was due primarily to the insufficient amount of Salton Sea and Atlantis II materials.…”
Section: Experimental Details and Resultscontrasting
confidence: 45%
“…A spontaneous fission activity that could not be explained by the known sources of the background, including uranium decay, was detected in some products of the chemical reprocessing of hot brines from Cheleken Peninsula (the South-East coast of the Caspean Sea [1]). There has been advanced the assumption that this activity is due to the decay of a naturally occurring nuclide belonging to the SHE region.…”
Section: Introductionmentioning
confidence: 98%
“…Flerov and coworkers investigated material from the Cheleken hot brines and have reported on the observation of a spontaneous fission activity in them using a 3He neutron-multiplicity counter arrangement [3]. We ([,1] and this paper) have made an attempt to find such an effect in hot brine deposits from the Atlantis II deep in the Red Sea [-4].…”
Section: Introductionmentioning
confidence: 92%